Preschool Teacher's Misconceptions about Games (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A teacher's knowledge about games is important in making sure that the games cause a positive impact on preschool children. Previous studies have proven that teachers know games as effectual learning tools for preshool children. However, little is known about the teachers’ knowledge on the types and features of the games which can give impact to preschool children. As such, this case study is conducted to find out preschool teachers’ knowledge on the types and features of the games. This study consists of quantitative and interview data. A questionnaire was used to gather responses from 30 preschool teachers all over Malaysia. Also, an interview protocol was used on three preschool teachers from different schools from Batu Pahat area. Correspondingly, a peer review was carried out for the purpose of trustworthiness of the data. The findings showed that the preschool teachers had the knowledge on the types and features of digital and non-digital games. Nevertheless, the teachers had a misconception about the games that they used. This implicates the needs to clearly rectify the preschool teachers’ misconception about the definition of games even though they have the knowledge on the types and features of digital and non-digital games.